2001
DOI: 10.3184/030823401103168884
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of Alcohols Catalysed by Heteropolyacids Supported on Silica

Abstract: Keggin type heteropolyacids supported on silica efficiently dehydrated secondary and tertiary alcohols under mild conditions and in good yields to afford the correspondent alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The studied alcohols (1-6) are shown in figure 1, as well as alkenes (7)(8)(9)(10)(11)(12) and corresponding dimers (13)(14)(15)(16)(17)(18)(19).…”
Section: Dehydration Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studied alcohols (1-6) are shown in figure 1, as well as alkenes (7)(8)(9)(10)(11)(12) and corresponding dimers (13)(14)(15)(16)(17)(18)(19).…”
Section: Dehydration Reactionsmentioning
confidence: 99%
“…However, the intensity of the maximum at 1030 cm )1 decreased considerably as a result of interaction between the precursor and surface groups of the support. ) and the products of the dehydration reaction, alkenes (7)(8)(9)(10)(11)(12) and dimers (13)(14)(15)(16)(17)(18)(19).…”
Section: Support and Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In some cases, it has been found that not only olefin products, but also their dimerization derivatives were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are few works dealing with the 1-indanol dehydration in liquid-phase. For example, Tarlani et al [26] and E. Alesso et al [27] found that unsupported heteropolyacids catalysts were selective to the intramolecular dehydration of NOL into ENE. However, a consecutive and fast HP formation was observed on this type of catalysts and, as a consequence, a yield in indene of only 25% after 20 min was reached due to the formation of 2-(2 0 ,3 0 -dihydro-1 0 H-inden-1 0 -yl)-1H-indene.…”
Section: Introductionmentioning
confidence: 99%